A systematic review of the clinical effectiveness and cost-effectiveness of sensory, psychological and behavioural interventions for managing agitation in older adults with dementia - Gill Livingston; Lynsey Kelly; Elanor Lewis-Holmes; Gianluca Baio; Stephen Morris; Nishma Patel; Rumana Z Omar; Cornelius Katona; Claudia Cooper (Health Technology Assessment, 2014)
Background: Agitation is common, persistent and distressing in dementia and is linked with care breakdown. Psychotropic medication is often ineffective or harmful, but the evidence regarding non-pharmacological interventions is unclear. Objectives: We systematically reviewed and synthesised the evidence for clinical effectiveness and cost-effectiveness of non-pharmacological interventions for reducing agitation in dementia, considering dementia severity, the setting, the person with whom the intervention is implemented, whether the effects are immediate or longer term, and cost-effectiveness. Data sources: We searched twice using relevant search terms (9 August 2011 and 12 June 2012) in Web of Knowledge (incorporating MEDLINE); EMBASE; British Nursing Index; the Health Technology Assessment programme database; PsycINFO; NHS Evidence; System for Information on Grey Literature; The Stationery Office Official Documents website; The Stationery National Technical Information Service; Cumulative Index to Nursing and Allied Health Literature; and The Cochrane Library. We also searched Cochrane reviews of interventions for behaviour in dementia, included papers’ references, and contacted authors about ‘missed’ studies. We included quantitative studies, evaluating non-pharmacological interventions for agitation in dementia, in all settings. Review method: We rated quality, prioritising higher-quality studies. We separated results by intervention type and agitation level. As we were unable to meta-analyse results except for light therapy, we present a qualitative evidence synthesis. In addition, we calculated standardised effect sizes (SESs) with available data, to compare heterogeneous interventions. In the health economic analysis, we reviewed economic studies, calculated the cost of effective interventions from the effectiveness review, calculated the incremental cost per unit improvement in agitation, used data from a cohort study to evaluate the relationship between health and social care costs and health-related quality of life (DEMQOL-Proxy-U scores) and developed a new cost-effectiveness model. Results: We included 160 out of 1916 papers screened. Supervised person-centred care, communication skills (SES = –1.8 to –0.3) or modified dementia care mapping (DCM) with implementing plans (SES = –1.4 to –0.6) were all efficacious at reducing clinically significant agitation in care home residents, both immediately and up to 6 months afterwards. In care home residents, during interventions but not at follow-up, activities (SES = –0.8 to –0.6) and music therapy (SES = –0.8 to –0.5) by protocol reduced mean levels of agitation; sensory intervention (SES = –1.3 to –0.6) reduced mean and clinically significant symptoms. Advantages were not demonstrated with ‘therapeutic touch’ or individualised activity. Aromatherapy and light therapy did not show clinical effectiveness. Training family carers in behavioural or cognitive interventions did not decrease severe agitation. The few studies reporting activities of daily living or quality-of-life outcomes found no improvement, even when agitation had improved. We identified two health economic studies. Costs of interventions which significantly impacted on agitation were activities, £80–696; music therapy, £13–27; sensory interventions, £3–527; and training paid caregivers in person-centred care or communication skills with or without behavioural management training and DCM, £31–339. Among the 11 interventions that were evaluated using the Cohen-Mansfield Agitation Inventory (CMAI), the incremental cost per unit reduction in CMAI score ranged from £162 to £3480 for activities, £4 for music therapy, £24 to £143 for sensory interventions, and £6 to £62 for training paid caregivers in person-centred care or communication skills with or without behavioural management training and DCM. Health and social care costs ranged from around £7000 over 3 months in people without clinically significant agitation symptoms to around £15,000 at the most severe agitation levels. There is some evidence that DEMQOL-Proxy-U scores decline with Neuropsychiatric Inventory agitation scores. A multicomponent intervention in participants with mild to moderate dementia had a positive monetary net benefit and a 82.2% probability of being cost-effective at a maximum willingness to pay for a quality-adjusted life-year of £20,000 and a 83.18% probability at a value of £30,000. Limitations: Although there were some high-quality studies, there were only 33 reasonably sized (> 45 participants) randomised controlled trials, and lack of evidence means that we cannot comment on many interventions’ effectiveness. There were no hospital studies and few studies in people’s homes. More health economic data are needed. Conclusions: Person-centred care, communication skills and DCM (all with supervision), sensory therapy activities, and structured music therapies reduce agitation in care-home dementia residents. Future interventions should change care home culture through staff training and permanently implement evidence-based treatments and evaluate health economics. There is a need for further work on interventions for agitation in people with dementia living in their own homes. Protocol registration: The study was registered as PROSPERO no. CRD42011001370. Funding: The National Institute for Health Research Health Technology Assessment programme.